QUALITY CONTROL IN IMPROVING PRODUCT QUALITY IN THE FINISHED GOODS WAREHOUSE OF PT. INDOFOOD NOODLE DIVISION SEMARANG USES THE PDCA (PLAN-DO-CHECK-ACTION) METHOD - Hotliana Dewi Sari Saragih; Luluk Fauziah (International Journal of Economic Integration and Regional Competitiveness, 2024)
With the progress of modern times, the competition between companies is becoming more and more stringent, one of which is seen from the quality of the goods produced, to produce goods of quality then the control of the products produced is carried out. This research was carried out at Indofood CBP Successful Wealth Noodle Division Semarang where many defective items were still found in the warehouse so that control and repair processes on defective products and goods were still needed. The purpose of this research is to know the quality control (Quality Control) in improving the quality in the finished goods warehouse as well as to know obstacles in enhancing the quality of the products produced, where the company needs to carry out the control of the product quality because there are still many defects in the warehouse of finished products. This research uses qualitative research methods with a descriptive approach. Research data sources use primary and secondary data sources used as information sources. In data collection by conducting field observations, interviews and documentation. The results of this study show that quality controls on products have been carried out from raw materials to the delivery of products to consumers, but can not be said well because there are still found defects on the products produced, caused by humans, machines, and methods, so there is still need to improve on controls, methods and machines